Strategies for Conducting Community Forums - Lisa A. Guion (EDIS)
Community forums are wonderful vehicles for obtaining input from county or area clientele groups about the needs, issues, problems, and/or future directions for Extension programming. A community forum can supplement secondary data/statistics (analyzed needs) by enabling educators to learn the expressed needs/issues/problems of their clientele groups and stakeholders. The first article in this series, Community Forums: An Effective Program Planning Tool (PD059), provides more detailed information about the value and benefits of, and two methods for, conducting community forums. This second article in the series presents key strategies for conducting community forums as well as ways to avoid potential pitfalls that hinder the effectiveness of community forums. This document is PE071, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, UF/ IFAS, Gainesville, FL 32611: First published: October 2003.